2022
DOI: 10.1038/s41416-022-02013-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the selective A2AR and A2BR dual antagonist AB928/etrumadenant on CAR T cell function

Abstract: Background Chimeric antigen receptor (CAR) T cell therapy has been successfully translated to clinical practice for the treatment of B cell malignancies. The suppressive microenvironment of many malignancies is a bottleneck preventing treatment success of CAR T cells in a broader range of tumours. Among others, the immunosuppressive metabolite adenosine is present in high concentrations within many tumours and dampens anti-tumour function of immune cells and consequently therapeutic response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…To assess direct ACh-CD8+ T cell interaction, we measured intracellular cytokine production following acute (4 h) ACh exposure as described ( 27 , 36 ). Splenic lymphocytes were expanded with IL2 or CD3/CD28 as reported ( 43 ). ACh exposure reduced CD8+ T cell production of TNFα, but not IL10, in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess direct ACh-CD8+ T cell interaction, we measured intracellular cytokine production following acute (4 h) ACh exposure as described ( 27 , 36 ). Splenic lymphocytes were expanded with IL2 or CD3/CD28 as reported ( 43 ). ACh exposure reduced CD8+ T cell production of TNFα, but not IL10, in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…25 Cotargeting A 2A R/A 2B R promotes activation and effector function of T cells in adoptive cell therapy. 26 This evidence strongly demonstrates that dual blockade of immunosuppressive A 2A R and A 2B R signaling is a promising strategy to overcome adenosine-mediated immunosuppression in cancer. Several small-molecule A 2A R/A 2B R dual antagonists have been reported (Figure 1), and the efficacy of these antagonists in alleviating immunosuppression in preclinical models or clinical trials in cancer has been described.…”
Section: ■ Introductionmentioning
confidence: 89%
“…It is reported that antitumor CD8 + T cells express the cAMP-boosting functional A 2A R and A 2B R, promoting T cell dysfunction . Co-targeting A 2A R/A 2B R promotes activation and effector function of T cells in adoptive cell therapy . This evidence strongly demonstrates that dual blockade of immunosuppressive A 2A R and A 2B R signaling is a promising strategy to overcome adenosine-mediated immunosuppression in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CD73 creates adenosine from several precursors, including NAD-derived cADPR, after NAD + has been processed by CD38 to carry out signaling activities [ 55 ]. Adenosine produced by CD73 has potent anti-inflammatory effects, including suppressing T cell function [ 56 , 57 ]. This is evidenced by reports of silencing CD73 in cultured lymphocytes resulting in a pro-inflammatory phenotype [ 58 ].…”
Section: Extracellular Nad + In Inflammatory Respo...mentioning
confidence: 99%